THE ANALYSIS OF THE TRANSMISSION MECHANISM OF MONETARY POLICY IN CONVENTIONAL AND SHARIA AGAINST INFLATION IN INDONESIA - Julika Rahma Siagian (Universitas Negeri Medan, 2020)
This study aims to analyze the transmission mechanism of monetary policy in Indonesia in controlling inflation, both in terms of sharia and conventional terms. The data used in this empirical study is time series data during 2011:1-2017:4 originating from (Bank Indonesia), Financial Services Authority (FSA) and Ministry of Finance (Kemenkue). The analysis tool used is the Error Correction Model (ECM). This study analyzes the relationship between independent and dependent variables both in the short and long term. The results of this study throuht the asset prices indicate that from conventional monetary variable SBI (certifikat of bank indonesia) variables that have a positive and significant effect on inflation in the short-term. Where as in the long term the variable money supply has a positive effect and variable interest rates on Bank Indonesia, bonds have a positive and significant effect on inflation. In Islamic monetary variables, SBIS have a positive and significant effect on inflation in the short-term. Islamic bond variables (Sukuk) have a negative and significant effect on inflation in the short-term. While in the long-term the variable money supply, Islamic interest rates, and Islamic bonds have a positive and significant effect on inflation.